2, 5-Diaryl-1, 3, 4-oxadiazoles as selective COX-2 inhibitors and anti-inflammatory agents1. Issue 56 (19th June 2015) - Grover, Jagdeep; Bhatt, Nirav; Kumar, Vivek; Patel, Neeraj K.; Gondaliya, Bhagirath J.; Elizabeth Sobhia, M.; Bhutani, Kamlesh K.; Jachak, Sanjay M.
<x xml:space="preserve">Abstract</x> A new series of compounds comprising of 2, 5-diaryl-1, 3, 4-oxadiazoles was synthesized and evaluated as potential COX-2 inhibitors.